Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.15244/pjoes/101615
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Herbicide Diuron in Pineapple-Growing Soils of Eastern Thailand

Abstract: Nowadays, social direction focuses on natural and organic farming, which bans or restricts the use of pesticides. However, chemicals such as herbicides and insecticides are still importantly essential in crop and livestock productions-particularly in the tropics, where severe outbreaks of weeds and pests are common and threaten the loss of such productions. Diuron (N-(3,4-dichlorophenyl)-N, N-dimethylurea) is the main systemic phenyl urea herbicide which inhibits the photosynthesis at PS II of plants [1-2]. Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
2
0
1
Order By: Relevance
“…Diuron is a non-ionic herbicide that shows high retention in soil and high affinity for organic matter via hydrophobic interactions [53], justifying the higher affinity for straw compared to diclosulam (Figure 1). In general, the sorption of diuron is greater in soils with higher organic matter content [54]. The partitioning of diuron at the soil/solution interface (Kd sorption) varies depending on the soil types in which the diuron is applied.…”
Section: Discussionmentioning
confidence: 99%
“…Diuron is a non-ionic herbicide that shows high retention in soil and high affinity for organic matter via hydrophobic interactions [53], justifying the higher affinity for straw compared to diclosulam (Figure 1). In general, the sorption of diuron is greater in soils with higher organic matter content [54]. The partitioning of diuron at the soil/solution interface (Kd sorption) varies depending on the soil types in which the diuron is applied.…”
Section: Discussionmentioning
confidence: 99%
“…Although many previous studies have reported sorption outcomes for diverse organic compounds, few studies have focused on emerging stormwater and roadway-derived contaminants despite their ubiquity and sometimes high concentrations. , Also, the high concentrations (e.g., milligrams per liter) frequently used to facilitate analytical detection in laboratory studies ,, often substantially exceed environmental concentrations. To address these data gaps, we investigated the sorption–desorption characteristics of ≤11 stormwater-derived contaminants.…”
Section: Introductionmentioning
confidence: 99%
“…O diuron é um herbicida não-iônico que apresenta alta retenção no solo e alta afinidade pela matéria orgânica por interações hidrofóbicas Karickhoff, 1990) o que justifica a maior afinidade pela palhada que o diclosulam (Figura 3.3). De maneira geral, a sorção do diuron é maior em solos com maiores teores de matéria orgânica (Tantarawongsa;Ketrot, 2020). A partição do diuron na interface solo/solução (Kdsorção) varia em função dos tipos de solos em que o diuron é aplicado.…”
Section: 1)unclassified